Evaluation and Classification of Behavioral Biases According to Thinking Styles, Risky Investment Intention, and Subjective Financial Literacy - Aren, Selim; Hamamci, Hatice Nayman (ISTANBUL UNIV, SCH BUSINESS, 2023)
The main purpose of this study is to classify the 20 biases into different groups (factors) and estimate each of them finance, which combines the concepts and approaches of psychology with the theory of finance, evaluates individuals' into four groups according to the variables of thinking style, risky investment intention, and subjective financial literacy investment intention and their levels of subjective financial literacy. In addition, it was also investigated whether both bias groups and other variables differed according to four demographic variables.
Keywords: Behavioral Biases; Thinking Styles; Risky Investment Intention; Subjective Financial Literacy; TAKING BEHAVIOR; REGRET-AVERSION; DECISION-MAKING; INDIVIDUAL-DIFFERENCES; COGNITIVE BIASES; OVERCONFIDENCE; GENDER; AVAILABILITY; FEEDBACK; IMPACT; Business & Economics